Binding Affinity and Driving Forces for the Interaction of Calixarene-Based Micellar Aggregates With Model Antibiotics in Neutral Aqueous Solution - Migliore, Rossella; Granata, Giuseppe; Rivoli, Andrea; Consoli, Grazia Maria Letizia; Sgarlata, Carmelo (Frontiers in Chemistry, 2021)
The search for novel surfactants or drug delivery systems able to improve the performance of old generation antibiotics is a topic of great interest. Self-assembling amphiphilic calix[4]arene derivatives provide well-defined nanostructured systems which exhibit promising features for antibiotics delivery. In this work, we investigated the capability of two micellar polycationic calix[4]arene derivatives to recognize and host ofloxacin, chloramphenicol or tetracycline in neutral aqueous solution. The formation of the nanoaggregates and the host-guest equilibria were examined by nano-isothermal titration calorimetry, dynamic light scattering and mono- and bi-dimensional NMR. The thermodynamic characterization revealed that the calix[4]arene-based micellar aggregates are able to effectively entrap the model antibiotics and enabled the determination of both the species and the driving forces for the molecular recognition process. Indeed, the formation of the chloramphenicol-micelle adduct was found to be enthalpy driven, whereas entropy drives the formation of the adducts with both ofloxacin and tetracycline. NMR spectra corroborated ITC data about the positioning of the antibiotics in the calixarene nanoaggregates.